Estimating thermal energy loads in remote and northern communities to facilitate a net-zero transition. (1st March 2023) - Maynard, Ian; Abdulla, Ahmed
Abstract: Canada has more than 350 remote and northern communities, most of which rely on diesel for their electric and thermal needs. This reliance is deleterious to climate, health, albedo, and energy security—all diesel must be imported. The government is working to transition these communities to climate-friendly and sustainable alternatives, but assessments of this transition are hampered by limited data availability, especially the absence of hourly thermal load profiles. Here, we develop a method for estimating the thermal load profiles of these communities; apply it to 40 communities that vary across characteristics like population, location, accessibility, and Indigenous identity; and seek to validate these profiles with the few empirical data that exist. We also develop a model to predict the thermal load of a remote and northern community using limited, available information like population and location. This paper represents the first attempt to simulate hourly thermal load profiles for these communities. We find that thermal loads are large—the hourly thermal load can be up to 23 times the hourly electrical load in winter, which has implications for investment planning. Our research helps communities, investors, and analysts develop robust transition plans as they seek to decarbonize northern communities' energy systems.